2014
DOI: 10.2478/s11687-014-0227-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating antigens in serum samples of mice experimentally infected with Trichinella spiralis by a sandwich ELISA based on IgY

Abstract: SummaryIn the present study, a sandwich ELISA based on IgY (egg yolk immunoglobulin) was developed for detection of circulating antigens (CAg) in sere of mice experimentally infected with Trichinella spiralis. The IgY-sandwich ELISA assay involved the use of chicken antibody IgY against excretory-secretory (ES) antigens of Trichinella spiralis muscle larvae as a capture antibody and mouse polyclonal antibody IgG to ES antigens as a detecting antibody. This method was able to detect as little as 3 ng/ml of ES a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Also, Wang et al (2012) found that T. spiralis circulating antigen was detected as early as 3 dpi in the serum of mice infected with 500 T. spiralis muscle larvae, and its level increased gradually and reached two peaks with detection rate of 40% and 100% at 13 and 24 dpi, respectively. Furthermore, Jing et al (2014) reported that T. spiralis circulating antigen was detectable as early as 8 dpi then increased radically during 13-15 dpi, peaking at 22 dpi in serum of mice infected with 500 larvae. The best cutoff of quantitative PCR in prediction of severe infection was ≥ 2.5841 with area under curve of 0.9, sensitivity of 80%, specificity of 81.5%, positive predictive value of 78.3%, negative predictive value of 83%, and overall accuracy of 80.8% (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Wang et al (2012) found that T. spiralis circulating antigen was detected as early as 3 dpi in the serum of mice infected with 500 T. spiralis muscle larvae, and its level increased gradually and reached two peaks with detection rate of 40% and 100% at 13 and 24 dpi, respectively. Furthermore, Jing et al (2014) reported that T. spiralis circulating antigen was detectable as early as 8 dpi then increased radically during 13-15 dpi, peaking at 22 dpi in serum of mice infected with 500 larvae. The best cutoff of quantitative PCR in prediction of severe infection was ≥ 2.5841 with area under curve of 0.9, sensitivity of 80%, specificity of 81.5%, positive predictive value of 78.3%, negative predictive value of 83%, and overall accuracy of 80.8% (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Wang et al (2012) found that T. spiralis circulating antigen was detected as early as 3 dpi in the serum of mice infected with 500 T. spiralis muscle larvae, and its level increased gradually and reached two peaks with detection rate of 40% and 100% at 13 and 24 dpi, respectively. Furthermore, Jing et al (2014) reported that T. spiralis circulating antigen was detectable as early as 8 dpi then increased radically during 13–15 dpi, peaking at 22 dpi in serum of mice infected with 500 larvae.…”
Section: Discussionmentioning
confidence: 99%